One for All - Overbeck, Jennifer R.; Droutman, Vitaliya (Psychological Science, 2013)
We argue that powerful people tend to engage in social projection. Specifically, they self-anchor: They use the self as a reference point when judging others’ internal states. In Study 1, which used a reaction-time paradigm, powerful people used their own traits as a reference when assessing the traits of group members, classifying group descriptors more quickly if they had previously reported that those terms described themselves. Study 2, which used a classic false-consensus paradigm, showed that powerful people believed that their group-related attitudes were shared by group members. Study 3 showed that more-powerful people relied more on their own state affect when judging other people’s ambiguous emotional expressions. These results support our argument that power fosters self-anchoring, because powerful individuals are often called on to act as the representative face of their groups, and the association between power and representation prompts the heuristic use of the self to infer group properties.